Analisis Produktivitas Tenaga Kerja Pada Pelaksanaan Pembangunan Rumah Sakit UPT Vertikal Makassar - Ivon Panggalo; M. Natsir Abduh; Savitri Prasandi Mulyani (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
The factors determining productivity include physical capital, human capital, natural resources, knowledge, and technology. The productivity of labor in the construction work of the UPT Vertical Makassar Hospital is influenced by wage levels, experience, worker skills, worker education, worker age, procurement of materials, and interpersonal relationships among workers. This study was conducted to assess the comparative values of field labor productivity, Indonesian National Standards, Minister of Public Works and Spatial Planning regulations, and the level of productivity in rebar work, formwork, and concrete pouring. The research uses a quantitative method, specifically analyzing the comparison of labor productivity. The study reveals significant differences between field productivity and productivity based on benchmarks. For rebar work, field productivity compared to the Indonesian National Standards is 39.648 times and compared to the Minister of Public Works and Spatial Planning regulations is 79.312 times. For formwork work, the comparison of field productivity with the Indonesian National Standards is 1.172 times, and with the Minister of Public Works and Spatial Planning regulations is also 1.172 times. The same value for formwork work is due to the identical coefficients used in the Indonesian National Standards and Minister of Public Works and Spatial Planning regulations. For column concrete work, the comparison of field productivity with the Indonesian National Standards is 1.409 times, and with the Minister of Public Works and Spatial Planning regulations is 1.007 times.